Arabidopsis RAB geranylgeranyl transferase beta-subunit mutant is constitutively photomorphogenic, and has shoot growth and gravitropic defects - Hála, Michal; Soukupová, Hana; Synek, Lukás; Zárský, Viktor (Plant journal, 2010)
RAB GTPases are important directional regulators of intracellular vesicle transport. Membrane localization of RAB GTPases is mediated by C-terminal double geranylgeranylation. This post-translational modification is catalyzed by the alpha-beta-heterodimer catalytic core of RAB geranylgeranyl transferase (RAB-GGT), which cooperates with the RAB escort protein (REP) that presents a nascent RAB. Here, we show that RAB-geranylgeranylation activity is significantly reduced in two homozygous mutants of the major Arabidopsis beta-subunit of RAB-GGT (AtRGTB1), resulting in unprenylated RAB GTPases accumulation in the cytoplasm. Both endocytosis and exocytosis are downregulated in rgtb1 homozygotes defective in shoot growth and morphogenesis. Root gravitropism is normal in rgtb1 roots, but is significantly compromised in shoots. Mutants are defective in etiolation and show constitutive photomorphogenic phenotypes that cannot be rescued by brassinosteroid treatment, similarly to the det3 mutant that is also defective in the secretory pathway. Transcriptomic analysis revealed an upregulation of specific RAB GTPases in etiolated wild-type plants. Taken together, these data suggest that the downregulation of the secretory pathway is interpreted as a photomorphogenic signal in Arabidopsis.
Keywords: proteiny huseníčku; transferasy; Prenylation; Arabidopsis; rekombinantní fúzní proteiny; prenylace; Arabidopsis Proteins; Gravitropism; Plant Shoots; Transferases; gravitropismus; výhonky rostlin; Recombinant Fusion Proteins